Association of Gestational Age at Birth With Risk of Perinatal Mortality and Special Educational Need Among Twins. Issue 10 (October 2020) - Murray, Sarah; MacKay, Daniel; Stock, Sarah; Pell, Jill; Norman, Jane
Abstract : (Abstracted from JAMA Pediatr 2020;174(5):437–445) Twin pregnancies are associated with higher rates of perinatal mortality and neonatal death and approximately 15% of admissions to neonatal and special care baby units. Current literature and policies are unclear on the ideal timing of birth for twins to optimize short-term clinical outcomes and long-term childhood outcomes, such as special education needs (SENs).